Systemic Risks in the Global Financial System and their Influence on Economic Stability - Oleksyn, Artur; Obikhod, Svitlana; Berezhynskyi, Denys; Pikus, Ruslana; Smereka, Svitlana (Economic Affairs, 2024)
The modern global financial system is defined by a high level of integration and interaction between countries, which creates a favorable environment for the flow of capital and trade. However, this integration also creates systemic risks that can seriously undermine financial stability. Systemic risks affect key aspects of the global economy and may have further consequences for the economic stability of countries and regions. In this context, the analysis of systemic risks in the global financial system becomes of great importance to identify and understand their impact on economic stability and to develop strategies to overcome and counter these risks. The academic paper focuses on systemic risks in the global financial system and their impact on economic stability. In particular, it examines various aspects of these risks, assessing their potential impact on key segments of the global economy. The importance of analyzing such risks for the development of effective management strategies and the prevention of possible crises is emphasized. In addition, by evaluating the results of systemic risk monitoring, the research contributes to the understanding of their impact on economic stability and formulating strategies to counter and overcome these threats. The general approach to this study is aimed at highlighting key aspects and determining priority areas of action to ensure the stability of the financial system in conditions of global instability.
Keywords: Systemic risks, globalization, global financial system, economic stability, macroeconomic imbalances, risk monitoring, financial stresses, financial sector